The effects of social media towards democratization in Tunisia and Jordan (2018-2020) / Nursyuhada Zulkifli and Farhatul Mustamirrah Mahamad Aziz - Zulkifli, Nursyuhada; Mahamad Aziz, Farhatul Mustamirrah (2021)
Another Mass protest occurred within several parts of MENA such as Jordan and Tunisia due to several reasons that may be connected to the 2011 Arab Spring. According to Marwan Muasher (2019), a huge road protest was initiated by the public in the matter of gaining the attention of the government to make further changes. The promises have been made by the government in the 2011 Arab Spring has not yet been fully fulfilled. Most of the promises are barely propaganda that has been proposed by the government to reducing the tense of the public riot. Therefore, the public has decided to initiate another protest as a matter of demanding the government to fulfill their role and responsibilities towards the public since the issues of tax levitation, poverty, and increasing rate of unemployment remain unsettled until now. The process has been done in rather a peaceful manner at the beginning until the involvement of tear gas caused the whole scenario to flip. Hence, the purpose of this paper is to delve into the role of social media towards pursuing democratization governance in Tunisia and Jordan and to examine the effectiveness of social media towards strengthening democratic governance in Tunisia and Jordan.